Answer :

Let the polynomial to be subtracted be ax2 + bx + c

3x2 + 5x – 4 = (x2 + 13x + 7) - (ax2 + bx + c)


(ax2 + bx + c) = (x2 + 13x + 7) – (3x2 + 5x – 4)


= (x2 – 3x2) + (13x – 5x) + (7 + 4)


= -2x2 – 8x + 11


Comparing with coefficients we get:


a= -2


b = -8


c = 11


Therefore, the polynomial is = -2x2 -8x + 11


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

Write the correctMHB - Math Part-I

Write the degree MHB - Math Part-I

Write the followiMHB - Math Part-I

Subtract the secoMHB - Math Part-I

Write the followiMHB - Math Part-I

Write the index fMHB - Math Part-I

Add the followingMHB - Math Part-I

Write the correctMHB - Math Part-I

Write the correctMHB - Math Part-I

Write the correctMHB - Math Part-I